Slow-release N fertilisers are not an alternative to urea for fertilisation of autumn-grown tall cabbage - Rodrigues, M.A. (2010)
Tall cabbage (Brassica oleracea var. costata, cv. Penca de Mirandela) is grown in Portugal during autumn and winter months when heavy rains can be expected. In this agrosystem the management of N is a considerable challenge due to the risk of nitrate leaching. Field experiments with tall cabbage and rye were carried out during the growing seasons of 2007/2008 and 2008/2009. The experimental design included three fertilisers that delay N availability by different mechanisms [Floranid permanent, containing isobutylidene diurea (IBDU); Basacote, a polymer-coated fertiliser; and Entec 26, containing 3,4-dimethylpyrazole phosphate (DMPP) as nitrification inhibitor], two urea treatments (total N applied basally; and divided into two equal rates in preplant and topdress application), and a zero N control. The fertilisers were applied at a rate of 120 kg N ha−1. A pot experiment with tall cabbage followed by ryegrass grown in the same pots was carried out in 2007/2008. The fertiliser treatments were essentially the same and a rate of 2.94 g N/pot was applied. Dry matter yield, plant N concentration, plant N recovery and indices of N-use efficiency were compared among the fertiliser treatments. In the pot experiment, soil nitrate concentration was also monitored by using anion exchange membranes inserted directly into the soil. Urea produced mean DM yields statistically higher than control in all crops and in both field and pot experiments and years. No significant differences in DM yield were usually found among fertilised treatments. Basacote produced DM yields often not significantly different from that of control. In the field experiment of tall cabbage, plants recovered 20 and 50% of the amount of N applied, respectively in Basacote and in the other fertilised plots. In the pot experiment, tall cabbage + ryegrass recovered 49.6 and ≈100% of N applied, respectively in Basacote and in the other fertilised plots. From the strictly agronomic point of view, none of the slow-release N materials provided advantages over urea to be advised for this agrosystem, considering also their high cost.